Phase Separation and Disorder-to-Order Transition of Human Brain Expressed X-Linked 3 (hBEX3) in the Presence of Small Fragments of tRNA. Issue 7 (27th March 2020) - do Amaral, Mariana J.; Araujo, Talita S.; Díaz, Nuria C.; Accornero, Federica; Polycarpo, Carla R.; Cordeiro, Yraima; Cabral, Katia M.S.; Almeida, Marcius S.
Abstract: Brain Expressed X-linked (BEX) protein family consists of five members in humans and is highly expressed during neuronal development. They are known to participate in cell cycle and in signaling pathways involved in neurodegeneration and cancer. BEX3 possess a conserved leucine-rich nuclear export signal and experimental data confirmed BEX3 nucleocytoplasmic shuttling. Previous data revealed that mouse BEX3 auto-associates in an oligomer rich in intrinsic disorder. In this work, we show that human BEX3 (hBEX3) has well-defined three-dimensional structure in the presence of small fragments of tRNA (tRFs). Conversely, the nucleic acids-free purified hBEX3 presented disordered structure. Small-angle X-ray scattering data revealed that in the presence of tRFs, hBEX3 adopts compact globular fold, which is very distinct from the elongated high-order oligomer formed by the pure protein. Furthermore, microscopy showed that hBEX3 undergoes condensation in micron-sized protein-rich droplets in vitro . In the presence of tRFs, biomolecular condensates were smaller and in higher number, showing acridine orange green fluorescence emission, which corroborated with the presence of base-paired nucleic acids. Additionally, we found that over time hBEX3 transits from liquid condensates to aggregates that are reversible upon temperature increment and dissolved by 1, 6-hexanediol. hBEX3 assemblies display different morphology in the presence of the tRFs that seems to protect from amyloid formation. Collectively, our findings support a role for tRFs in hBEX3 disorder-to-order transition and modulation of phase transitions. Moreover, hBEX3 aggregation-prone features and the specificity in interaction with tRNA fragments advocate paramount importance toward understanding BEX family involvement in neurodevelopment and cell death. Graphical abstract: Unlabelled Image